2010
DOI: 10.3748/wjg.v16.i31.3957
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of CT angiography in diagnosing acute gastrointestinal bleeding: A meta-analysis

Abstract: CT angiography is an accurate, cost-effective tool in the diagnosis of acute GI bleeding and can show the precise location of bleeding, thereby directing further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
2
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 31 publications
3
73
2
6
Order By: Relevance
“…Despite the small sample size, this study proved that helical CT angiography is an easier and faster technique than conventional angiography for localizing GI bleeding and is useful as a guide for subsequent selective angiography [4]. Subsequently, Yoon et al [5] demonstrated an accuracy of 88.5 % (22/26) for the detection of acute GI bleeding using multidetector row CT. Wu et al [3] and Anthony et al [2] proposed that CT angiography should be used routinely for the investigation of patients who meet the criteria for acute GI hemorrhage due to its high accuracy and the ability to show the precise location and etiology of bleeding, thereby directing management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the small sample size, this study proved that helical CT angiography is an easier and faster technique than conventional angiography for localizing GI bleeding and is useful as a guide for subsequent selective angiography [4]. Subsequently, Yoon et al [5] demonstrated an accuracy of 88.5 % (22/26) for the detection of acute GI bleeding using multidetector row CT. Wu et al [3] and Anthony et al [2] proposed that CT angiography should be used routinely for the investigation of patients who meet the criteria for acute GI hemorrhage due to its high accuracy and the ability to show the precise location and etiology of bleeding, thereby directing management.…”
Section: Discussionmentioning
confidence: 99%
“…However, bleeding can recur in 25 % of cases, causing significant morbidity and mortality [3]. Hospital mortality for acute GI hemorrhage is 10 %, but this can reach up to 30 % with massive bleeding associated with hemodynamic instability or in patients who rebleed during hospitalization [3]. These patients require further intervention, imaging localization, and directed therapy to secure hemostasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…L'angio-TDM abdominale permet actuellement de diagnostiquer avec une bonne sensibilité une hémorragie digestive aiguë abondante. La visualisation d'une extravasation de produit de contraste dans le tube digestif permet d'affirmer l'hémorragie et de préciser son siège, permettant ainsi la planification d'un éventuel geste thérapeutique [5]. L'angio-TDM représente donc une excellente alternative en cas d'hémorragie grave non diagnostiquée par l'endoscopie.…”
Section: Discussionunclassified